Spinal Cord Lesion by Minor Trauma as an Early Sign of Multiple System Atrophy - Brum, Marisa; Reimão, Sofia; Sousa, Djalma; de Carvalho, Rui; Ferreira, Joaquim J. (Frontiers in Neurology, 2016)
Multiple System Atrophy (MSA) is characterized clinically by parkinsonism, cerebellar, autonomic and corticospinal features of variable severity. When the presentation is only parkinsonism, the disease might be difficult to differentiate from Parkinson´s Disease (PD). We present a case of an 80-year-old man with previous diagnosis of PD. One year after diagnosis he had a whiplash cervical trauma due to a tricycle accident caused by a hole in the road. This low-energy trauma caused an unstable C4-C5 cervical fracture with spinal cord injury which required surgical decompression and stabilization. Neurological examination showed marked postural instability, no rest and postural tremor, finger tapping slowed on the right, spastic tetraparesis (ASIA D)—predominantly on the left side—, brisk deep tendon reflexes in the upper and lower extremities and bilateral extensor plantar response. He also presented with vertical gaze restriction, mild hypometria in horizontal saccades, moderate dysphagia and dysphonia. As atypical parkinsonism was suspected he underwent an MRI which revealed conjunction of findings suggestive of parkinsonian-type multiple system atrophy (MSA). In our case we hypothesise that the loss of postural reflexes, as an early manifestation of MSA, did not allow the patient to have an effective reaction response to a low-energy trauma, resulting in a more severe injury. With this case report we speculate that the severe spinal lesions caused by minor accidents can be an early sign of postural instability, which may lead to clinical suspicion of neurodegenerative disorder manifested by postural reflexes impairment.